Analysis and design of PID Control System for Active Magnetic Bearings - Adil H. Ahmed; Thamir M. Abdul Wahab (Engineering and Technology Journal, 2009)
Active magnetic bearings (AMB) are unstable by their nature and are used in veryhigh-speed applications, therefore the design and implementation of a suitable control systemfor such devices requires extensive investigation. In this paper the AMB control problem istreated and design method of proportional plus derivative plus integral (PID) control system isproposed using the two degrees of freedom method. The designed PID control system issimulated and tested using MATLAB/Simulink, and some practical effects are investigated